Efficient synthesis of dipeptide analogues of α-fluorinated β-aminophosphonates - Kaźmierczak, Marcin; Koroniak, Henryk (Beilstein Journal of Organic Chemistry, 2020)
Herein, we present an efficient synthesis of dipeptide analogues of α-fluorinated β-aminophosphonates. Each step of the synthesis was optimized to provide excellent yields. Moreover, the absolute configuration of the obtained compounds was determined by X-ray analysis, which proved the stereochemistry that was proposed based on NMR studies.
Keywords: dipeptide analogues; fluorinated aminophosphonates; fluorine; nucleophilic fluorination; phosphorus

(untitled) - Romanenko, V. D.; Kukhar, V. P. (Chem. Rev., 2006)

(untitled) - Turcheniuk, K. V.; Kukhar, V. P.; Röschenthaler, G.-V.; Aceña, J. L.; Soloshonok, V. A.; Sorochinsky, A. E. (RSC Adv., 2013)

(untitled) - Cytlak, T.; Kaźmierczak, M.; Skibińska, M.; Koroniak, H. (Phosphorus, Sulfur Silicon Relat. Elem., 2017)

(untitled) - Song, B.-A.; Wu, Y.-L.; Yang, S.; Hu, D.-Y.; He, X.-Q.; Jin, L.-H. (Molecules, 2003)

(untitled) - Rao, X.; Song, Z.; He, L. (Heteroat. Chem., 2008)

(untitled) - Herczegh, P.; Buxton, T. B.; McPherson, J. C.; Kovács-Kulyassa, Á.; Brewer, P. D.; Sztaricskai, F.; Stroebel, G. G.; Plowman, K. M.; Farcasiu, D.; Hartmann, J. F. (J. Med. Chem., 2002)

(untitled) - Yang, S.; Gao, X.-W.; Diao, C.-L.; Song, B.-A.; Jin, L.-H.; Xu, G.-F.; Zhang, G.-P.; Wang, W.; Hu, D.-Y.; Xue, W.; Zhou, X.; Lu, P. (Chin. J. Chem., 2006)

(untitled) - Berkowitz, D. B.; Bose, M. (J. Fluorine Chem., 2001)

(untitled) - Berkowitz, D. B.; Bose, M.; Pfannenstiel, T. J.; Doukov, T. (J. Org. Chem., 2000)

(untitled) - Nieschalk, J.; Batsanov, A. S.; O'Hagan, D.; Howard, J. (Tetrahedron, 1996)

(untitled) - Nieschalk, J.; O'Hagan, D. (J. Chem. Soc., Chem. Commun., 1995)

(untitled) - Tarasenko, K. V.; Romanenko, V. D.; Sorochinsky, A. E. (J. Fluorine Chem., 2018)

(untitled) - Berkowitz, D. B.; Bose, M.; Asher, N. G. (Org. Lett., 2001)

(untitled) - McKenna, C. E.; Shen, P.-D. (J. Org. Chem., 1981)

(untitled) - Blackburn, G. M.; Kent, D. E. (J. Chem. Soc., Chem. Commun., 1981)

(untitled) - Blackburn, G. M.; England, D. A.; Kolkmann, F. (J. Chem. Soc., Chem. Commun., 1981)

(untitled) - Ni, C.; Hu, M.; Hu, J. (Chem. Rev., 2015)

(untitled) - Champagne, P. A.; Desroches, J.; Hamel, J.-D.; Vandamme, M.; Paquin, J.-F. (Chem. Rev., 2015)

(untitled) - Hu, W.-L.; Hu, X.-G.; Hunter, L. (Synthesis, 2017)

(untitled) - Nielsen, M. K.; Ugaz, C. R.; Li, W.; Doyle, A. G. (J. Am. Chem. Soc., 2015)

(untitled) - Nielsen, M. K.; Ahneman, D. T.; Riera, O.; Doyle, A. G. (J. Am. Chem. Soc., 2018)

(untitled) - Bennua-Skalmowski, B.; Vorbrüggen, H. (Tetrahedron Lett., 1995)

(untitled) - Vorbrüggen, H. (Synthesis, 2008)

(untitled) - Guo, J.; Kuang, C.; Rong, J.; Li, L.; Ni, C.; Hu, J. (Chem. – Eur. J., 2019)

(untitled) - Montalbetti, C. A. G. N.; Falque, V. (Tetrahedron, 2005)

(untitled) - Valeur, E.; Bradley, M. (Chem. Soc. Rev., 2009)

(untitled) - Pattabiraman, V. R.; Bode, J. W. (Nature, 2011)

(untitled) - El-Faham, A.; Albericio, F. (Chem. Rev., 2011)

(untitled) - Albericio, F.; El-Faham, A. (Org. Process Res. Dev., 2018)

(untitled) - Kaźmierczak, M.; Koroniak, H. (J. Fluorine Chem., 2012)

(untitled) - Kaźmierczak, M.; Kubicki, M.; Koroniak, H. (Eur. J. Org. Chem., 2018)

(untitled) - Pudovik, A. N.; Konovalova, I. V. (Synthesis, 1979)

(untitled) - Rádai, Z.; Keglevich, G. (Molecules, 2018)

(untitled) - Bailey, P. D.; Beard, M. A.; Dang, H. P. T.; Phillips, T. R.; Price, R. A.; Whittaker, J. H. (Tetrahedron Lett., 2008)

(untitled) - Kaźmierczak, M.; Kubicki, M.; Koroniak, H. (J. Fluorine Chem., 2014)

(untitled) - Kafarski, P.; Lejczak, B. (Synthesis, 1988)

(untitled) - Vaidhyanathan, R.; Natarajan, S.; Rao, C. N. R. (J. Mol. Struct., 2002)

(untitled) - Spingler, B.; Schnidrig, S.; Todorova, T.; Wild, F. (CrystEngComm, 2012)

(untitled) - Sheehan, J. C.; Hess, G. P. (J. Am. Chem. Soc., 1955)

(untitled) - König, W.; Geiger, R. (Chem. Ber., 1970)

(untitled) - Sheehan, J.; Cruickshank, P.; Boshart, G. (J. Org. Chem., 1961)

(untitled) - Wehrstedt, K. D.; Wandrey, P. A.; Heitkamp, D. (J. Hazard. Mater., 2005)

(untitled) - Jad, Y. E.; Khattab, S. N.; de la Torre, B. G.; Govender, T.; Kruger, H. G.; El-Faham, A.; Albericio, F. (Eur. J. Org. Chem., 2015)

(untitled) - Subirós-Funosas, R.; Prohens, R.; Barbas, R.; El-Faham, A.; Albericio, F. (Chem. – Eur. J., 2009)

(untitled) - El-Faham, A.; Funosas, R. S.; Prohens, R.; Albericio, F. (Chem. – Eur. J., 2009)

CrysAlis PRO, version 1.171.38.41 (Rigaku Oxford Diffraction, 2015)

(untitled) - Sheldrick, G. M. (Acta Crystallogr., Sect. A: Found. Crystallogr., 2008)

(untitled) - Kaźmierczak, M.; Kubicki, M.; Koroniak, H. (Phosphorus, Sulfur Silicon Relat. Elem., 2016)